A Meta-Analysis: The Effect of Emotional Intelligence on Students' Mathematics Learning Outcomes in Indonesia - Aljura, Ahmad Naufal; Retnawati, Heri; Widjajanti, Djamilah Bondan (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Yogyakarta, 2024)
This study aimed to determine the effect size of emotional intelligence on student learning outcomes in Mathematics learning, described research trends based on categories, and described emotional intelligence scales (instruments) used in Mathematics learning. This research used a quantitative approach with the method of Systematic Literature Review with Meta-Analysis. The data collected for the qualitative descriptive were 14 research articles and for the combined effect size analysis were 11 articles. It was found that the research trend on the effect of emotional intelligence on Mathematics learning outcomes has increased from 2015 to 2022. The results of the analysis showed that the significant effect of Emotional Intelligence on students' Mathematics learning outcomes was categorized as